080 The incidence, diagnosis and outcomes of idiopathic intracranial hypertension in the southern tasmanian catchment. (29th July 2019) - Krishnadas, Natasha; Taylor, Bruce
Abstract : Introduction: This study aimed to identify the incidence of idiopathic intracranial hypertension (IIH) in Southern Tasmania, Australia. Secondary aims were to elucidate demographics, current approaches to investigation, treatment and outcomes. To our knowledge, similar regional studies have not been performed. Methods: The study was approved by the University of Tasmania Human Ethics Committee. Patients presented between June 2016-June 2018 to Royal Hobart Hospital, the single tertiary Neurology service in Tasmania. Cases were identified by screening lumbar punctures (LP) performed by Neurology services (inpatient, outpatient, Radiologically-assisted) and by surveying all regional Neurologists. Medical records were used to corroborate LP results and determine whether patients met Modified Dandy Criteria (MDC) (used to define IIH in current literature). Regional population statistics were obtained from the Australian Bureau of Statistics (ABS). Duplicate records were excluded. Exclusion criteria included age <18 at data collection, LP opening pressure <20cm of water or secondary causes for IIH. Results: 45 cases identified; 30 within the Greater Hobart region, population of 229, 088 (June 2016-June 2017). Cumulative incidence was 6.55/100, 000 (incidence rate 0.06/1000) with classification based on Neurologist diagnosis and 5.46/100, 000 (0.05/1000) with classification according to MDC. 100% of the cohort were female. Mean age was 26.7 (range 17–45) and mean weight was 105.3kg (range 78–170). Headache was the most commonly reported symptom. 8.9% (4/45) of the total cohort were medically refractory (requiring VP/LP shunting). Ophthalmology services initiated 51% (23/45) of the referrals. Conclusions: Our incidence rates are higher than rates in previous studies for population subsets of young women.